2017
DOI: 10.3390/soc7030022
|View full text |Cite
|
Sign up to set email alerts
|

Leisure for People with Disabilities in Rural Quebec

Abstract: Leisure is an instrument used to facilitate the social integration of people with disabilities. However, it requires significant knowledge of the needs and expectations of this clientele, who often experience isolation, especially in rural areas. The general objective of this study was to attempt to identify and understand the realities experienced by the partners of the Quebec Association for Leisure for People with Disabilities, who offer various services and leisure activities to people with disabilities in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…Noraini (2006) mentioned that even the activity for leisure time is necessary in one's personal life, but most of the researchers frequently ignore this issue. Moreover, most of the researcher's study leisure among students, disabilities, tourists, women and aged (Reddy, Vranda, Ahmed, Nirmala, & Siddaramu, 2010;Ryan & Glendon, 1998;Roult et al, 2017;Brown & Frankel, 1993) in the eastern and western context.…”
Section: Problem Statementmentioning
confidence: 99%
See 1 more Smart Citation
“…Noraini (2006) mentioned that even the activity for leisure time is necessary in one's personal life, but most of the researchers frequently ignore this issue. Moreover, most of the researcher's study leisure among students, disabilities, tourists, women and aged (Reddy, Vranda, Ahmed, Nirmala, & Siddaramu, 2010;Ryan & Glendon, 1998;Roult et al, 2017;Brown & Frankel, 1993) in the eastern and western context.…”
Section: Problem Statementmentioning
confidence: 99%
“…Besides, the researchers have rarely focused on the other factors that might influence one's leisure. The most frequently investigated factors include demographic characteristic (Deem, 1986;Henderson & Shaw, 2006), personal factor (Dridea & Sztruten, n.d), friends and family, time factor (Bammel & Burrus-Bammel, 1996) and the environmental factor (Roult et al, 2017) of the individual. There is no known past research that has been found to use the work and family domain as the independent variables to influence one's leisure satisfaction in Malaysia.…”
Section: Problem Statementmentioning
confidence: 99%